The Dynamics of Educational Leadership Acculturation: A Fiel Study with Peter L. Berger Social Construction Approach - Ivan Riyadi; Khoirul Anam Siddeh; Musdiani Musdiani; Yana Dwi Christanti; Moh Thohir (Newinera Publisher, 2026)
This study investigates the dynamics of educational leadership acculturation at MA Al-Fatah Palembang through the lens of Peter L. Berger’s social construction theory. Using a qualitative field study design, the research explores how school leaders internalize, construct, and institutionalize leadership values within the cultural, religious, and organizational contexts of the madrasah. Data were collected through in-depth interviews, observation, and documentation, involving principals, vice principals, teachers, and student organization leaders. The findings reveal that leadership practices at MA Al-Fatah are shaped by a continuous dialectic process: externalization of Islamic-based leadership values, objectivation through institutional rituals and organizational norms, and internalization by individuals within the school community. These processes foster a hybrid form of leadership that integrates traditional Islamic values with contemporary educational management practices. The study also highlights factors that support and hinder acculturation, including organizational culture, leadership communication, teacher participation, and stakeholder engagement. Overall, the research provides theoretical and practical insights into how leadership identities are socially constructed and negotiated within Islamic educational settings.